Developing an improver of targeted action for the prolonged freshness of bread made from wheat flour - Bilyk, Olena; Kochubei-Lytvynenko, Oksana; Bondarenko, Yuliia; Vasylchenko, Tetyana; Pukhlyak, Anastasia (My University, 2020)
The development of a complex bakery improver "Freshness CDP SUPER" (Ukraine) to slow down the staling of products developed for accelerated technologies is urgent. It contains nutritional supplements with GRAS status. Whey protein concentrate "CDP-UV-65" was chosen as a functional basis. The active part contains the enzyme preparation Novamil 1500MG, maltodextrin, defatted sunflower lecithin, carboxymethyl cellulose, apple pectin, dry wheat gluten and ascorbic acid. It is proved that with rational dosage of the developed complex bakery improver in the amount of 1.5% to the flour mass, the bread production process is reduced by 180 minutes. It has been established that the bread "Milk Freshness", the recipe of which includes the developed improver, is characterized by a higher specific volume by 10.1% in comparison with the control, porosity, and better shape stability of hearth products. It has been proven that products with the addition of the Freshness CDP SUPER complex bakery improver retain freshness longer, which is confirmed by a 47% greater total crumb deformation compared to the control. The inhibition of staling in bread "Milk Freshness" occurs due to the accumulation of dextrin by 27.1% compared with the control. Thus, the total content of dextrins in wheat bread is 1.918% to DS, and in Milk Freshness bread - 2.438% to DS.The research results prove the expediency of using the complex bakery improver "Freshness CDP SUPER" in the technology of wheat bread in order to extend the preservation period of its freshness up to 72 hours in unpackaged form.
Keywords: complex bakery improver; wheat bread; staling; dextrin; functional base; active part; кафедра технології хлібопекарських і кондитерських виробів; кафедра технології молока і молочних продуктів